Pengembangan Profesionalisme Guru Berkelanjutan Pasca Sertifikasi Di SMK PGRI 1 Ngawi (Studi pada Guru-Guru Bersertifikat Pendidik di SMK PGRI 1 Ngawi) - HADI, Farid Samsul, Prof. Bambang Sumardjoko, M,Pd (2015)
The aims of these research are to describe: (1) to describe teachers professionalism after sertification, (2) to know the efforts of the teachers to improve their sustainable professionalism after sertification, (3) to know the obstacle that the teachers faced in improving their sustainable professionalism after sertification, (4) to describe the teachers alternative solution in improving their sustainable professionalism after sertification. This is a qualitative research by using ethnografi method. The method used in this research are interview methode, observation, and documentation. To check the validity of the data the researcher used triangulation data. This research data analysis techniques includes: collecting, data presentation, data reduction and finding the conclusion or verivication. The conclusion of this research are: (1) The professionalism of teachers at SMK PGRI 1 Ngawi can be observed with the availability of a teaching device, the liveliness of a certified teacher educator at MGMP activities, seminars, training, and other scientific activities. Moreover certified teacher educators in SMK PGRI 1 Ngawi also carry out action research and scientific writing and innovative work, although not yet published, (2) a description of the efforts made by a certified teacher educators in the context of professional development looks to boost stakeholders for teachers who want to develop themselves through further studies, writing scientific papers and manufacture of innovative work, although not yet fully maximized, (3) to the obstacles teachers at SMK PGRI 1 Ngawi can be described that to develop the professionalism of teachers there are still obstacles related to the limited time because of the burden of teaching in schools, limited ability and knowledge related to the research, scientific writing and innovative works, (4) as an alternative solution can be described that every effort is made to drop support for professional development of teachers, including policy makers, principals, and although the government is still not optimal.